An Analysis of the Role of Rhizobacteria that Promote Plant Growth in Agricultural Sustainability: Exploring the Impact of Rhizobacteria on Plant Growth for Sustainable Agriculture (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sustainable agriculture involves the effective use of agricultural capital to meet evolving human needs while preserving or improving environmental sustainability and preserving natural resources. Plant Growth Use The promotion of rhizobacteria will play an impotent function in achieving the sustainable agriculture objectives. Rhizobacteria are known as Rhizosphere-resident bacteria. The goal is to research the function of Rhizobacteria and promote plant growth in farming sustainable development.